Mengintegrasikan Nilai Keberlanjutan dan Moderasi Beragama dalam Manajemen Perubahan Perguruan Tinggi Islam di Indonesia - Agus Setyawanto; Bachtiar Hariyadi; Sufinatin Aisida (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2026)
This study explores the integration of sustainability and religious moderation values in change management practices at Islamic higher education institutions in Indonesia. Using a qualitative case study approach involving 15 key informants from academic and administrative sectors, the research identifies four main themes: awareness and commitment to sustainable change, the role of religious moderation in shaping organizational culture, communication and stakeholder participation strategies, and challenges faced during change implementation. Findings indicate that embedding sustainability and religious moderation enhances organizational adaptability, inclusivity, and long-term transformation success. However, resistance from individuals accustomed to the status quo and limited resources remain significant obstacles. The study underscores the importance of combining technical change management models with cultural-religious values to foster effective and harmonious organizational change in Islamic educational contexts.